HITEMAL-an outer sheath material for MgB2 superconductor wires: The effect of annealing at 595–655 °C on the microstructure and properties. (5th November 2018) - Balog, Martin; Rosova, Alica; Szundiova, Bronislava; Orovcik, Lubomir; Krizik, Peter; Svec, Peter; Kulich, Miloslav; Kopera, Lubomir; Kovac, Pavol; Husek, Imrich; Ibrahim, Ahmed Mohamed Hassan
Abstract: An aluminum material stabilized with a 1.6 vol% of nanometric Al2 O3 dispersoids, named HITEMAL, was fabricated by hot extrusion of a fine atomized Al powder. The Al2 O3 dispersoids stemmed from a native Al2 O3 films on an aluminum powder surface. An extruded rod of the material was then cold-deformed out into a thin wire by rotatory swaging, hydro extrusion and rolling. Such severely deformed HITEMAL was studied as a prospective outer sheath stabilizer material for MgB2 core superconductor wires. An emphasis was put on the effect of annealing realized at various temperatures close to the melting point of Al, which is typically applied to form an in-situ MgB2 superconductive core, on the mechanical and electrical properties of the HITEMAL wire. A systematic investigation was performed of changes to a severely deformed Al grain structure and Al2 O3 dispersoids upon annealing the as-deformed wire from 595 to 655 °C for 30 min. Mechanical and electrical properties of the wire were measured at room and cryogenic temperatures. The results showed that the ultrafine-grained Al + 1.6 vol% Al2 O3 wire exhibited advantageous properties, and surface integrity after annealing up to 642 °C. It is thus a lightweight material of choice for outer sheaths of MgB2 superconductors. Graphical abstract: Unlabelled Image Highlights: Al wire fabricated from a fine Al powder was studied as outer sheath material for lightweight MgB2 superconductors. The effect of annealing realized at 595-655 °C on microstructure, mechanical and electrical properties was investigated. The as-rolled wire showed ultrafine-grained Al structure with 1.6% of nanometric Al2 O3 dispersoids dispersed in Al matrix. The Al2 O3 dispersoids effectively stabilized Al grain structure during annealing, and only minor Al grain growth occurred. Wires annealed up to 642 °C showed attractive strength and electrical resistivity at room and cryogenic temperatures.